Мужчина в окне напротив: роман / Олег Рой - Рой Олег (Капризы и странности судьбы, 2018)
Экземпляры: аб. ЦБ (20211125) / Инвентарный номер: 11858 / Цена: / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Р 65 / ББК: 84(2=411.2)6-44